The practices and effectiveness of strategic leadership as perceived by the educational leaders at selected secondary schools in Selangor - Nazifah Alwani Binti Mohamad (Institute of Education,International Islamic University Malaysia, 2012)
The aim of this research is to investigate the practices and effectiveness of strategic leadership among school principals as perceived by educational leaders from the selected seventy (70) secondary schools in Selangor which have attained high academic achievement particularly in the Penilaian Menengah Rendah (PMR) from 2008 to 2010. The framework of the study is based on the model by Davies and Davies in Davies et al. (2005). As suggested by the model, the practices and effectiveness of strategic leadership have been assessed from two dimensions; the organisational abilities and individual characteristics. In addition, there are nine important components which are connected to both dimensions that indicate the successful activities and behaviours of strategic leaders. Questionnaire has been used as the research instrument. The study utilised 35 items on the strategic leadership styles developed by Davies and. Davies in 2004. From the total of 175 respondents who participated in the study, there were 36 principals and 139 senior assistants. The findings indicated that the practice and effectiveness of strategic leadership as perceived by the principals are indeed at very high level, whereby all the components of organisational abilities and individual characteristic~ are already in place. In addition, the findings have revealed a higher 'perception on the existence of the components of the strategic leadership amongst the principals rather than the senior assistant which puts a lesser degree of perception on the existence of the components of strategic leadership. This study discovered that the most outstanding element of strategic leadership was the component of restlessness. It has dominated not only most of the result of the principals' practices of strategic leadership as perceived by. principals and senior assistants, but also in terms of the principals' effectiveness as indicated by both groups of respondents. This study has also revealed that there is no significant difference between strategic leadership practice and effectiveness in terms of gender, experience and position of respondents. Moving forward, this study will indeed serve as an important tool to examine and measure the impacts of strategic leadership practices on school achievement as perceived by the educational leaders. This is significant particularly in shifting their schools to a higher level in tandem with the government's National Key Result Area (NKRA) for education as pronounced by the government of Malaysia recently. Eventually, this study provides valuable insights into the strategic development processes and approaches which are utilised by effective strategic educational leaders towards the betterment of the nation.